Resolving Field Development & Management Challenges in Large Heterogenous Reservoirs Using Segment Models - Kelechi, Ihekoronye Kingsley; CN, Izuwa; KK, Ihekoronye; BO, Obah (Journal of Advanced Research in Petroleum Technology & Management, 2021)
Characterizing and modeling flow-critical features continues to pose significant challenge for reservoir description, modeling and performance prediction especially in large heterogeneous reservoirs. The level of details that can be incorporated in models has been constrained by limitation in computing capability, runtime and ability to interpret model outputs. In spite of large sums of money spent on ‘destabilization’ of the reservoir geological description, but due mainly to computing limitations, we have to drop most of the flow critical information in the process of reservoir modeling and simulation. The need to capture significant low level details around specific portions of the reservoir which details would otherwise be lost if the entire geological model was up-scaled, led to the carving out and building of models of tiny portions of the reservoir for more detailed study. This study demonstrates the viability and application of segmenting the reservoir for the purpose of detailed flow simulation aimed at resolving reservoir management challenges in a Niger delta large reservoir where performance has indicated significant heterogeneity requiring more focused ‘small area’ studies. There is no published or reported use of this method in studying Niger Delta reservoir performance possibly because of perceived “homogeneity” of the reservoirs. It is however expected that as most of the reservoirs mature and field performance deviates from expectations, the need for more detailed and granular characterization and modeling will become apparent and resort to techniques such as this imperative. The methodology involved cutting up the reservoir into portions for more detailed characterization, building fit-for-purpose models that included all flow-critical features while honoring appropriate boundary conditions and simulating performance of the mini-reservoir. Results from this “mini-reservoir”studies were then scaled up and applied in resolving field challenges. Application of the workflow above gave meaningful insight into reservoir flow physics and well performance. This has aided performance forecasting and helped in answering questions around well-spacing, well standoff and possible alternative depletion strategies for the XY field. This study clearly shows that where properly designed and applied,segment models are a veritable and useful tool for providing insight to reservoir flow physics and performance. Results are scalable and should be used wherever possible and appropriate as it is less costly and time efficient. How to cite this article: Nwakwue JE, Izuwa NC, Ihekoronye KK et al. Resolving Field Development & Management Challenges in Large Heterogenous Reservoirs Using Segment Models. J Adv Res Petrol Tech Mgmt 2019; 5(1): 24-33.